Heights of Cumulonimbus cloud tops over North India: A Radar study - KULSHRESTHA, S. M. (MAUSAM, 1962)
In India, the only information on heights of cumulonimbus cloud tops, available so far, is based on very limited number of observations either from debriefing reports of aircrafts or from meteorological reconnaissance flights. To gain more exhaustive and complete knowledge of cumulonimbus cloud tops over North India, a radar study based on the record of the 469 storms observed during a period of 31 months, was conducted at New Delhi using the CPS-9 radar. The result of the analysis are detailed out and discussed in the light of the existing information on the subject.